Effect of band gap on TiO₂ thin film with different layer using dip coating technique / S.F.A Samat, M.S.P Sarah and M.F.M Idros - Samat, S.F.A; Sarah, M.S.P; Idros, M.F.M (Universiti Teknologi MARA, 2019)
Titania or titanium dioxide (TiO2) thin films were prepared using a simple sol-gel dip-coating method on a glass substrate. Titanium (IV) tetraisopropoxide, (TTIP) was used as a titania precursor. The purpose of this work is to study the behaviour of optical band gap with the different number of layer and the phase present of each sample. From the result, all samples are amorphous phase have their value of optical band gap in the range of 3.21 eV until 3.80 eV depends on transition. The number of layers increased caused the surface morphology of TiO2 to agglomerate and the roughness of the samples increased. The single layer sample shows higher transmittance value than multiple layer samples which is the best for optical sensor application.